2019
DOI: 10.6000/1929-7092.2019.08.97
|View full text |Cite
|
Sign up to set email alerts
|

The National Strategy on Financial Literacy: A Conceptual Review of South African Perspectives

Abstract: The relevance of financial literacy in the lives of individuals has attracted several stakeholders from different parts of the world in the quest to provide the required financial knowledge for households to manage their financial wellbeing. Accordingly, previous studies show that financial literacy serves as a mechanism to enhance the ability of households to better allocate financial resources with regard to savings and wealth creation over their lifetimes in a world of uncertainty and imperfect insurance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…These two objectives can be achieved if there is a training model and investment empowerment (Nicolini et al 2013). This is also in line with the thoughts of Ifeanyi et al (2019), Askar et al (2020), andNugraha (2020), which details the investment literacy and education coaching and training model through several activities, namely: (1) encouraging the training ecosystem in the school environment to equip students with the right knowledge to make the right investment decisions; and (2) encourage research and innovation, especially digital-based.…”
Section: Discussionsupporting
confidence: 73%
“…These two objectives can be achieved if there is a training model and investment empowerment (Nicolini et al 2013). This is also in line with the thoughts of Ifeanyi et al (2019), Askar et al (2020), andNugraha (2020), which details the investment literacy and education coaching and training model through several activities, namely: (1) encouraging the training ecosystem in the school environment to equip students with the right knowledge to make the right investment decisions; and (2) encourage research and innovation, especially digital-based.…”
Section: Discussionsupporting
confidence: 73%
“…Nanziri and Leibbrandt (2018) have found that financial literacy was positively associated with financial behavior, suggesting that improving financial literacy could lead to better financial decision-making. Similarly, Ifeanyi et al (2019) have developed a financial literacy index for South Africa based on the following six constructs namely: (1) financial management, (2) investment literacy, (3) borrowing literacy, (4) insurance literacy, (5) knowledge of financial products and services, and (6) knowledge of financial institutions and their functions.…”
Section: Constructs and Measures Of Financial Literacymentioning
confidence: 99%
“…Furthermore, South Africa has a number of financial education programmes and initiatives. However, these programmes lack unification and focus of efforts amongst different stakeholders (Ifeanyi, Rena & Prinsloo, 2019). The programmes are not supported by research on how to properly deliver and implement them, with most programmes being narrow, lacking depth and failing to represent South Africa's national interests, and lastly are not governed by best practices and standards for financial literacy education (Ifeanyi et al, 2019).…”
Section: The South African Basic Education Conundrummentioning
confidence: 99%
“…However, these programmes lack unification and focus of efforts amongst different stakeholders (Ifeanyi, Rena & Prinsloo, 2019). The programmes are not supported by research on how to properly deliver and implement them, with most programmes being narrow, lacking depth and failing to represent South Africa's national interests, and lastly are not governed by best practices and standards for financial literacy education (Ifeanyi et al, 2019). Consequently, there are not many financial literacy programmes at national level that are specifically designed for teachers/educators for long term results.…”
Section: The South African Basic Education Conundrummentioning
confidence: 99%